Woman in niqab and contestation of piety show-off in the media - Awanis Akalili; Wening Udasmoro; Ratna Noviani (Universitas Negeri Yogyakarta, 2023)
HIjrah is not only limited on human relation with God, but also how hijrah discourse existence is delivered in the media as discourse battle arena. Niqab is a characteristic of a woman going through hijrah. By using multimodality of Gunther Kress and Theo van Leuween, this critical discourse digs deeper on phenomena of woman in niqab and contestation of piety show-off in the media. Based on analysis performed on four accounts of woman with niqab in Instagram, narration found that the most massive show-off action of piety are performed by niqabis, that is in the act of religious activities, such as reading Al-Qur'an, praying, suggestion on sadaqa and five-times prayer. Moreover, piety representation is also performed by using quotes in Arabian language and Arabian woman figure as illustration to legitimate the hijrah journey of a woman in niqab. Piety, not only it displays woman in covering clothes, but also intersection with popular culture. It’s existence is put together with the incidentally profane Korean wave love romance This phenomena shows a paradox where there is incorporation of religious sacredness with the often considered profane Korean wave.